PENGARUH LATIHAN SQUAT JUMP TERHADAP POWER OTOT TUNGKAI PADA PEMAIN BOLA VOLLY TIM TWC KECAMATAN KUOK KABUPATEN KAMPAR - Munardi, Munardi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations from researchers in the field, Bolavoli from the Kuok District Team, Kampok District. The researcher observed that during the training and match sessions in the Kuok District Volleyball Team in Kampar District, the District was still not optimal. One of them is like a leg muscle when jumping when doing a smash or block. So when you do a smash or block is not optimal. The purpose of this study was to determine the effect of squat jump exercises on leg muscle strength in the Kuok sub-district volleyball team in Kampar District. The population in this study was a team of 12 people from the Kuok District volleyball team in the Kampar District. The sample is a small portion of the population that is the subject of research. In this study the sampling technique was done by means of total sampling. The instrument in this study is a vertical leap. Based on the analysis and discussion of data, it can be concluded that there is an effect of jump squat training on leg muscle strength. On the Twc volleyball team in Kuok Subdistrict, Kampar Regency, it is proven by the results of tcount 4.723> t table 1.796 at α = 0.05. This proves that by doing squat jump exercises, leg muscle strength can produce better results.Key Words: Squat Jump, Leg Muscle Strength